Targeting TGF-β signaling in the multiple myeloma microenvironment: Steering CARs and T cells in the right direction - Rana, Priyanka S.; Soler, David C.; Kort, Jeries; Driscoll, James J. (Frontiers in Cell and Developmental Biology, 2022)
Multiple myeloma (MM) remains a lethal hematologic malignancy characterized by the clonal expansion of malignant plasma cells within a permissive bone marrow (BM) microenvironment. The emergence of relapsed and/or refractory MM (RRMM) is provoked through clonal evolution of malignant plasma cells that harbor genomic, metabolic and proteomic perturbations. For most patients, relapsed disease remains a major cause of overall mortality. Transforming growth factors (TGFs) have pleiotropic biologic effects that regulate myelomagenesis as well as the emergence of drug resistance. Moreover, TGF- modulates numerous cell types present with the BM milieu, e.g., stromal cells, osteoblasts, osteoclasts, endothelial cells, and immune cells. While numerous agents have been FDA-approved over the past two decades and significantly expanded the treatment options available for MM patients, the molecular mechanisms responsible for drug-resistance remain elusive. MM is uniformly preceded by a premalignant state, monoclonal gammopathy of unknown significance, and both conditions are associated with progressive deregulation in host immunity characterized by reduced T-cell, NK cell and antigen-presenting DC functional activity. TGF- promotes myelomagenesis as well as intrinsic drug resistance by repressing anti-myeloma immunity to promote tolerance, drug resistance and disease progression. Hence, repression of TGF-β signaling is a prerequisite to enhance the efficacy of current and future immunotherapeutics. Novel strategies that incorporate T-cells engineered to express chimeric antigen receptor (CARs), T-cell receptors (TCRs) and bispecific T-cell engagers (BiTEs) offer promise to block TGF- signaling, overcome drug resistance and enhance anti-myeloma immunity. Here, we discuss the effect of TGF- signaling on immune cell effectors in the BM and emerging strategies to suppress TGF--mediated myeloma growth, drug resistance and survival.